THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER’S SATISFACTION AT PT. SINAR MUTIARA CAKRABUANA - Amna Amelia Oktaviani; Siti Nur Barokah; Sri Marhaeni Salsiyah (Politeknik Negeri Semarang, 2018)
The purpose of this research was to determine and analyze the influence of services quality: tangible (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) on customer’s satisfaction (Y) at PT. Sinar Mutiara Cakrabuana. The collecting data methods used in this research were questionnaires, interview and literature review. The scale of questionnaires used agree-disagree scale with 10 point scale and the respondents in this research were 90 samples. The sampling technique used is purposive sampling. The data analysis technique used was multiple linear regression. The result could be concluded that service quality which consists of tangible (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) has positive and significance influence on customer’s satisfaction (Y). Meanwhile the contribution of the independent variables (tangibles, reliability, responsiveness, assurance, empathy) on customer’s satisfaction was 66,7%.